2020
DOI: 10.12911/22998993/127094
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Agriculture Soils from High Andean Zones and Potential Ecological Risk Assessment in Peru's Central Andes

Abstract: Soil is exposed to heavy metals that are associated with the anthropogenic activities, and is currently an environmental and food safety problem. The concentration and source of heavy metals in soils, the level of contamination and the potential for ecological risk in high Andean ecosystems were evaluated. The soil samples were collected from the surface part in which Andean crops were sown and the concentration of As, Cd, Pb, Fe and Zn was quantified. The concentrations of heavy metals in soils did not exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…The results obtained reveal that soils in sectors S3 and S4 recorded PTE concentrations that exceeded the maximum permitted limits of the national and international standard ( MINEN, 2017 , FAO/WHO, 2011a , CME, 2004 , EPMC, 2014 ), which means that the soils in these sectors are undergoing degradation processes. The mean concentrations of As, Pb and Zn in this study were higher than the concentrations reported by Orellana et al (2020) in high Andean areas with rainfed agriculture in the central region of Peru. The high concentration of Pb and As in sectors S3 and S4 reveal that the bioavailable concentration of heavy metals is higher in soils irrigated with contaminated water than in soils irrigated with rainwater.…”
Section: Discussioncontrasting
confidence: 91%
“…The results obtained reveal that soils in sectors S3 and S4 recorded PTE concentrations that exceeded the maximum permitted limits of the national and international standard ( MINEN, 2017 , FAO/WHO, 2011a , CME, 2004 , EPMC, 2014 ), which means that the soils in these sectors are undergoing degradation processes. The mean concentrations of As, Pb and Zn in this study were higher than the concentrations reported by Orellana et al (2020) in high Andean areas with rainfed agriculture in the central region of Peru. The high concentration of Pb and As in sectors S3 and S4 reveal that the bioavailable concentration of heavy metals is higher in soils irrigated with contaminated water than in soils irrigated with rainwater.…”
Section: Discussioncontrasting
confidence: 91%
“…Relatively high Zn and Pb contents lead to correspondingly higher geoaccumulation index values. The ecological risk index mainly considers the toxicity of the different heavy metals [9] . Additionally, the toxic response factors of Cd and Hg are much higher than those of other heavy metals, which leads to larger E i values for Cd and Hg.…”
Section: Potential Ecological Risk Index Resultsmentioning
confidence: 99%
“…There are many severe problems due to soil contamination in China, particularly related to heavy metals [8]. Because of the toxicity, bioaccumulation and persistence of heavy metals, they pose a significant threat to the natural environment [9] . Understanding the concentration and spatial distribution of soil heavy metals and assessing their ecological risks are critical for the accurate and effective implementation of risk management and control of soil heavy metal pollution [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential ecological risk index method [ 27 , 45 ] was used to evaluate the potential ecological risks of soil PHEs obtained through sedimentation from coking waste gas in BTH (Equations (8) and (9)). where is the potential ecological risk index of a single PHE i ; is the toxicity coefficient of PHE i , and the coefficients of As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn are 10, 30, 2, 5, 40, 5, 5, and 1, respectively [ 45 , 46 , 47 ]; is the concentration of a single PHE i , mg·kg −1 ; is a reference for a single PHE i , mg·kg −1 , which was the background value of PHEs in BTH; RI is the comprehensive potential ecological risk index of PHEs. Risk classification standards refer to published studies [ 45 , 48 ] ( Table S2, Supplementary File) .…”
Section: Methodsmentioning
confidence: 99%